MO153RENAL FUNCTIONS OUTCOME IN METASTATIC NON SMALL LUNG CARCINOMA PATIENTS: THE RISK OF AKI IN FIRST LINE THERAPY. (29th May 2021) - Trevisani, Francesco; Di Marco, Federico; Fiorio, Francesco; Cattaneo, Monica; Rijavec, Erika; Ghidini, Michele
Abstract: Background and Aims: The optimal use of immune and target therapies, the optimal use of standard chemotherapy (CT) is of paramount importance, especially for patients affected by chronic kidney disease (CKD) who require dose adjustment according to the glomerular filtration rate (GFR) to avoid acute kidney injury (AKI) establishment. Immune checkpoint inhibitors (ICIs) and platinum-based chemotherapy (CT) are options for the palliative treatment of metastatic non-small cell lung cancer (NSCLC). Recently, CT in combination with immune-checkpoint inhibitors has become the treatment of choice for this setting of patients. Therefore, it is fundamental to investigate the potential nephrotoxic effects of both treatments and their potential additive effects on renal function. Aim of our study was to compare the nephrotoxic effect of both ICIs and CT (cisplatin and carboplatin-based) in a consecutive cohort of patients affected by metastatic NSCLC. Method: A consecutive cohort of 126 patients treated in first-line for NSLCL was enrolled in a single tertiary Hospital between 2018 and 2020. Inclusion criteria were: age (> 18 years old), eGFR (> 15 ml/min/1.73), histological diagnosis of metastatic NSCLC. Each patient underwent immunotherapy or CT according to clinical conditions, comorbidities and programmed death ligand 1 (PD-L1) expression status. eGFR (using CKD-EPI formula 2009) was detected at baseline and after each cycle of immunotherapy or CT (using cisplatin or carboplatin) in order to determine the correct renal status using the K-DIGO 2012 guidelines for AKI stages and CKD classes. Pts were subdivided into CKD categories G according to their eGFR values before and after the treatment. AKI onset was evaluated by rise in creatine levels according to K-DIGO criteria. Clinical stage according to cTNM (AJCC TNM system-2019) was collected at baseline before the first treatment. Comorbidities (e.g., diabetes, blood hypertension, overweight and obesity) were also included. Comparison between numerical variables was performed using linear regressions; between groups using Kruskal-Wallis rank sum test for numerical variables and Pearson's Chi square test for categorical variables. Log rank test was used to test differences between groups in terms of AKI onset during the therapy. Results: Clinical and pathological characteristics are reported in table 1. From the analysis, no significative differences were detected between Immunotherapy and CT group for age, gender, basal serum creatinine, basal eGFR, basal BMI, diagnosis of diabetes, hypertension, basal CKD G group or overall AKI onset. Treatment cycles were significantly different between the two groups (p<0.001) with a short median number of cycles for the CT group. No significative difference in terms of decay of eGFR calculated as final-basal values was detected (p=0.8). AKI onset over cycles was significantly different between the two groups (p=0.02), observing a higher risk of developing earlier AKI for CT group (cisplatin or carboplatin) (13, 9%) with respect to immunotherapy (7, 4%) (figure 1 and 2 ). Conclusion: Our study highlights that both cisplatin and carboplatin-based CT displays an augmented incidence of AKI development after a lower number of therapy cycles in respect of immunotherapy. The nephrotoxic effects of combined therapy for NSLCL should be always evaluated by nephrologist during the treatment of NSLCL patients to avoid an augmented risk of AKI derived from the combination of immunotherapy and CT in first line.